Basiliximab treatment for steroid‐resistant rejection in pediatric patients following liver transplantation for acute liver failure. (14th October 2014) - Shigeta, Takanobu; Sakamoto, Seisuke; Uchida, Hajime; Sasaki, Kengo; Hamano, Ikumi; Kanazawa, Hiroyuki; Fukuda, Akinari; Kawai, Toshinao; Onodera, Masafumi; Nakazawa, Atsuko; Kasahara, Mureo
Abstract An IL‐2 receptor antagonist, basiliximab, decreases the frequency of ACR in liver transplant (LT) recipients as induction therapy. The aim of this study was to evaluate the effectiveness of basiliximab against SRR as rescue therapy in pediatric LT patients with ALF. Forty pediatric ALF patients underwent LT between November 2005 and July 2013. Among them, seven patients suffering from SRR were enrolled in this study. The median age at LT was 10 months (6–12 months). SRR was defined as the occurrence of refractory rejection after more than two courses of steroid pulse therapy. Basiliximab was administered to all patients. The withdrawal of steroids without deterioration of the liver function was achieved in six patients treated with basiliximab therapy without patient mortality, although one patient developed graft loss and required retransplantation for veno‐occlusive disease. The pathological examinations of liver biopsies in the patients suffering from SRR revealed severe centrilobular injuries, particularly fibrosis within one month after LT. We demonstrated the effectiveness and safety of rescue therapy consisting of basiliximab for SRR in pediatric LT recipients with ALF.